The Attribution Theory Of As a Psycho-Social Approach to thePerception of Occupational Health and Safety: A Focus GroupStudy Among Women Workers in Metal Industry - Aytac, Serpil; Akalp, Gizem (European Journal of Multidisciplinary Studies, 2022)
Nowadays, women involved in working life with the industrial revolutionprovide their labor as much as men and are affected by the risk factors in theworkplace as much as men. Women are more affected by the psycho-socialrisk factors because of gender roles and they are also more affect societybecause of important central role in the family. Psycho-social risks that is oneof the occupational health and safety risk factors affect employee attitude andperformance to work at least as much as the other risk factors. In this study,researchers aim that reveal awareness’s about psychosocial risk factors intheir workplace in metal industries in Turkey. In addition, negative attitudesof workers about occupational health and safety practices will be examinedwith attribution theories in social psychology. In this study, we usedqualitative method. Data were collected with focus group study at eightdifferent groups in two different days from woman member of Turkish MetalUnion in Bursa city in Turkey. Totally 155 employees participated in the focusgroups study. Job satisfaction, job stress, wellness, the relationship withcoworkers and managers were evaluated in this study. This study wassupported and funded (Project USIP (?) 2014/7) by the Scientific ResearchProjects Commission of Uludag University cooperated with Turkish MetalUnion. According to the obtained results, work stress emerges as an importantpsychosocial risk factor. In addition to, stress and lack of communication areimportant factors causing job dissatisfaction.
Keywords: Occupational Health and Safety, Psychosocial Risks, Women Workers, Metal Industry, Attribution theories